Predictors of Outcome in Neonates with Respiratory Distress - John, BM; Venkateshwar, V; Dagar, V (Journal of Nepal Paediatric Society, 2015)
Introduction: Many of the parameters utilised in scoring systems used to predict disease severity in respiratory distress in neonates are not readily available in the primary care facility of developing countries. This study was carried out to assess the utility of birth weight, gestational age, APGAR score at 5 min, baseline oxygen saturation and Downe’s score in prediction of requirement of respiratory support and mortality in neonates with respiratory distress. Material and Methods: A prospective study was carried out in the neonatal intensive care unit of a tertiary teaching hospital. 165 consecutively admitted neonates presenting with respiratory symptoms were included in the study. The relevant parameters and investigations were documented in a structured performa. The neonates were followed up for outcomes which included requirement of respiratory support and mortality. Results: A higher mortality was associated with birth weight of < 1620 grams, gestational age of < 31 weeks, APGAR score of < 6, Downe’s score of > 3 and baseline oxygen saturation of < 86 % (p values < 0.001). The requirement of mechanical ventilation was more with birth weight of < 2000 grams, gestational age of < 32 weeks, APGAR score of < 7, Downe’s score of > 4 and baseline oxygen saturation of < 87 % (p value < 0.001). The requirement of any respiratory support at 72 hours was associated with birth weight of < 1894 grams, gestational age of < 37 weeks, APGAR score of < 7, Downe’s score of > 3 and baseline oxygen saturation of < 89 % ( p-value <0.001). Conclusions: Readily available parameters like birth weight, gestational age, APGAR score, oxygen saturation and Downe’s score could together be used to predict mortality and requirement of respiratory support in the resource limited setting. J Nepal Paediatr Soc 2015;35(1):31-37